Maleng, Thai Insect Hunter - Pelz, Claudia (Marta Polo Mediaproduction, 2006)
Verzio FF submission The monsoon region of Isan is among the poorest areas of Thailand. The village Ban Sarng is located in the northeast, near the border with Laos, where local chef Pi Li makes specialties of insects. In the family manufacture, he also makes cosmetic preparations and medicines from insects.